Community Service and Voting Among Veterans and Nonveterans Using a National Sample of College Undergraduates. Issue 2 (April 2020) - Griffith, James
Research studies have shown an association between military service and later civic involvement, largely defined as political activities. The National Postsecondary Student Aid Study 2008 ( N = 95, 650) was used to compare veteran and nonveteran students on community service activities and voting. Proportionately more nonveteran than veteran students reported community service (i.e., working with children both in educational and noneducational settings and fund-raising). Nonveteran students also were more likely to have participated in community service in last 12 months. The two groups did not differ in average hours spent on community service per month (16 hr). Veterans compared to nonveterans were far more likely to have registered to vote (78% vs. 59%) and to have voted (90% vs. 82%). When gender, age, race, and income were considered in comparisons, previous differences were not statistically different. Results are discussed relative to past proposals and research regarding veterans' civic engagement.